Biomarkers and Mechanisms of FANCD2 Function. (29th April 2008) - Willers, Henning; Kachnic, Lisa A.; Luo, Chen-Mei; Li, Li; Purschke, Martin; Borgmann, Kerstin; Held, Kathryn D.; Powell, Simon N.
Abstract : Genetic or epigenetic inactivation of the pathway formed by the Fanconi anemia (FA) and BRCA1 proteins occurs in several cancer types, making the affected tumors potentially hypersensitive to DNA cross-linkers and other chemotherapeutic agents. It has been proposed that the inability of FA/BRCA-defective cells to form subnuclear foci of effector proteins, such as FANCD2, can be used as a biomarker to aid individualization of chemotherapy. We show that FANCD2 inactivation not only renders cells sensitive to cross-links, but also oxidative stress, a common effect of cancer therapeutics. Oxidative stress sensitivity does not correlate with FANCD2 or RAD51 foci formation, but associates with increased γ H2AX foci levels and apoptosis. Therefore, FANCD2 may protect cells against cross-links and oxidative stress through distinct mechanisms, consistent with the growing notion that the pathway is not linear. Our data emphasize the need for multiple biomarkers, such as γ H2AX, FANCD2, and RAD51, to capture all pathway activities.